A chemotaxonomic study of phytochemicals in Hedyotis corymbosa. (October 2015) - Li, Hongquan; Li, Chun; Xia, Bohou; Zhou, Yamin; Lin, Limei; Liao, Duanfang
Abstract: An investigation of Hedyotis corymbosa resulted in the isolation of eighteen compounds, including six iridoids (1 –6 ), six monocyclic phenols (7 –12 ), one triterpene (13 ), two sterols (14 –15 ), one anthranquinone (16 ), one oxylipin (17 ) and one coumarin (18 ). The compounds were identified as scandoside methyl ester (1 ), deacetyl asperulosidic acid (2 ), deacetyl asperulosidic acid methyl ester (3 ), daphylloside (4 ), 10- O -benzoyl deacetyl asperulosidic acid methyl ester (5 ), 10- O -benzoyl scandoside methyl ester (6 ), p -hydroxybenzaldehyde (7 ), 4-methoxybenzene-1, 2-diol (8 ), Z - p -hydroxyphenylacetyl (9 ), p -hydroxybenzoic acid (10 ), E - p -hydroxyphenylacetyl (11 ), protocatechuic acid (12 ), oleanic acid (13 ), daucosterol (14 ), β -sitosterol (15 ), 1-methoxy-2-hydroxyanthraquinone (16 ), (9R*, 10S*, 7E)-6, 9, 10-trihydroxyocta- dec-7-enoic acid (17 ) and hedyotiscone A (18 ). Compounds4, 7 –9, 11 and17 were isolated from H . corymbosa for the first time, compound8 was a new natural product. The chemotaxonomic significance of these compounds was summarized in the paper. The presence of (9R*, 10S*, 7E)-6, 9, 10-trihydroxyoctadec-7-enoic acid (17 ) in H . corymbosa could be used to differentiate it from Hedyotis diffusa . Compounds with a 10- O -benzoyl structure, such as compounds5 and6, could be used as typical components for quality control. Highlights: Compounds4, 7–9, 11 and17 were isolated from H . corymbosa for the first time. Compound8 was a new natural product. The presence of compound17 in H.corymbosa could be used to differentiate it from H. diffusa . It revealed that H . corymbosa and H . diffusa may be more closely related. The compounds with a 10- O -benzoyl structure can offer the typical components for the future standard research of H . corymbosa .